2010
DOI: 10.1186/1753-2000-4-20
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density in partially recovered early onset anorexic patients - a follow-up investigation

Abstract: Background and aimsThere still is a lack of prospective studies on bone mineral development in patients with a history of early onset Anorexia nervosa (AN). Therefore we assessed associations between bone mass accrual and clinical outcomes in a former clinical sample. In addition to an expected influence of regular physical activity and hormone replacement therapy, we explored correlations with nutritionally dependent hormones.Methods3-9 years (mean 5.2 ± 1.7) after hospital discharge, we re-investigated 52 fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 75 publications
(97 reference statements)
4
20
0
2
Order By: Relevance
“…Weight gain and/or restoration are associated with a significant increase in BMD after a year, as reported for most of the studies with a follow-up longer than 12 months [40,41,44,45,46,47]. This finding confirms the hypothesis that BMD gain is a slow process in adolescent females with AN, and longer time frames are required to detect improvements.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Weight gain and/or restoration are associated with a significant increase in BMD after a year, as reported for most of the studies with a follow-up longer than 12 months [40,41,44,45,46,47]. This finding confirms the hypothesis that BMD gain is a slow process in adolescent females with AN, and longer time frames are required to detect improvements.…”
Section: Discussionsupporting
confidence: 84%
“…In 2010, Schulze et al [46] reported their results of whole-body DXA scans performed in a retrospective non-controlled study of BMD in 52 adolescent females with AN, namely a significant improvement in total BMD after >36-months follow-up from baseline. This was associated with an increase in BMI across the whole sample, from 14.7 ± 1.9 kg/m 2 to 20.1 ± 2.8 kg/m 2 .…”
Section: Resultsmentioning
confidence: 99%
“…A desnutrição causa baixa DMO em mulheres jovens com AN. A rápida perda de massa óssea que ocorre nos primeiros seis meses da doença é bem documentada em mulheres anoréxicas adultas (20,21). No entanto, poucos estudos avaliaram a massa óssea em adolescentes com AN e TANE.…”
Section: Discussionunclassified
“…11 Among adult women with AN, those who developed the disease as adolescents have lower bone density measures than those who developed the disease later in life, supporting the critical relationship between adolescent nutritional intake, peak bone mass accrual and life-long bone health. 41 Although skeletal losses that occur during the course of AN can improve with recovery, 42 full recovery cannot always be expected. 1,2,3 …”
Section: Adolescent Vs Adult Skeletal Considerationsmentioning
confidence: 99%